U-Shaped Association Between Blood Pressure and Mortality Risk in ICU Patients With Atrial Fibrillation: The MIMIC-III Database - Shao, Ying; Hu, Jinzhu (Frontiers in Cardiovascular Medicine, 2022)
Background Existing evidence on the association between blood pressure (BP) and mortality risk in intensive care unit (ICU) patients with atrial fibrillation (AF) is scarce. Aim This study aimed to assess the associations between blood pressure (BP) and risks of in-hospital and all-cause mortality in ICU patients with AF. Methods A total of 2,345 records of patients with AF whose BP was monitored after admission to the ICU were obtained from the MIMIC-III database. Incidences were calculated for endpoints (hospital mortality, 7-day mortality, 30-day mortality, and 1-year mortality). We performed smooth curve and logistic regression analyses to evaluate the association between BP and the risk of each endpoint. Results Smooth curve regression showed that systolic blood pressure (SBP), mean arterial pressure (MBP), and diastolic blood pressure (DBP) followed U-shaped curves with respect to endpoints (hospital mortality, 7-day mortality, 30-day mortality, and 1-year mortality). The incidence of these endpoints was lowest at 110/70/55 mm Hg. There was an increased risk of 1-year mortality observed with BP > 110/70/55 mm Hg (SBP, odds ratio [OR] = 1.008, 95% CI 1.001–1.015, p = 0.0022; MBP, OR = 1.010, 95% CI 1.005–1.016, p < 0.001) after adjusting for age, sex, and medical history. In contrast, an inverse association between BP and the risk of 1-year mortality was observed with BP ≤ 110/70/55 mm Hg (SBP, OR = 0.981, 95% CI 0.974–0.988, p < 0.001; MBP OR = 0.959, 95% CI 0.939–0.979, p < 0.001; and DBP, OR = 0.970, 95% CI 0.957–0.983, p < 0.001). Conclusions We observed a U-shaped association between BP and in-hospital/all-cause mortality in ICU patients with AF. However, the underlying causes need to be investigated.